Eristalis (Eristalis) tenax Linnaeus 1758 - El-Hawagry, Magdi S.; Gilbert, Francis (Zenodo, 2019)
Eristalis ( Eristalis ) tenax Linnaeus, 1758 Musca tenax Linnaeus, 1758: 591. Type locality: Sweden. Conops vulgaris Scopoli, 1763: 354. Type locality: Slovenia. Musca porcina De Geer, 1776: 98. Unjustified new name of tenax. Musca apiformis Geoffroy, 1785: 488. Type locality: Sweden. Eristalis campestris Meigen, 1822: 387. Type locality: Germany & Austria. Eristalis hortorum Meigen, 1822: 387. Type locality: Germany. Eristalis sylvaticus Meigen, 1822: 388. Type locality: Austria. Eristalis vulpinus Meigen, 1822: 388. Type locality: Austria. Eristalis cognatus Wiedemann, 1824: 37. Type locality: India (Tranquebar). Eristalis sinensis Wiedemann, 1824: 37. Type locality: China. Eristalis nili Rondani, 1850: 166. Type locality: Egypt. Eristalis columbica Macquart, 1855: 108. Type locality: Colombia. Eristalis ventralis Thomson, 1869: 489. Type locality: China. Eristalis tenax var. alpinus Strobl, 1893: 185. Type locality: Austria. Eristalis claripes Abréu, 1924: 104. Type locality: Canary Is. Material examined : 1 male, Arish, 6.V.1934, leg. Shafik; 1 female, Ismailia, 7.IV.1926, leg. Tewfik; 1 female, Wadi Rishrash, 21.VI.1932, leg. Tewfik; [EFC]. World distribution : Cosmopolitan, known from all regions except the Antarctic. Egyptian localities : Coastal Strip: Alexandria, Mariout. Eastern Desert: Ismailiya, Wadi Hoff, Wadi Rishrash. Fayoum: Fayoum City, Kom Osheem. Lower Nile Valley & Delta: Cairo, El-Gebel El-Asfar, El-Marg, Embaba, Ezbet El-Nakhl, Kombira, Shubra. Sinai: El-Arish. [Sources: Efflatoun 1922, Shaumar & Kamal 1978 and the examined museum material]. Activity period in Egypt : Throughout the year. Remarks : E. tenax is the most widely distributed syrphid in Egypt (Efflatoun 1922). Adults fly up to 5m from ground, spending a considerable amount of time resting on flowers and foliage, and in the evenings can be found sunning on the foliage of bushes and shrubs (Speight 2017). A wide range of flowers is visited by this species, including white, yellow, pink and blue blooms (De Buck, 1990). The rat-tailed larvae filter bacteria from water polluted by decaying organic matter, such as sewage treatment ponds (Aguilera et al . 1999). : Published as part of El-Hawagry, Magdi S. & Gilbert, Francis, 2019, Catalogue of the Syrphidae of Egypt (Diptera), pp. 201-248 in Zootaxa 4577 (2) on pages 222-223, DOI: 10.11646/zootaxa.4577.2.1, http://zenodo.org/record/2629643 : {"references": ["Linnaeus, C. (1758) Systema Naturae per regna tria naturae, secundum classes, ordines, genera, species, cum characteribus, differentiis, synonymis, locis. Editio decima, reformata. Tomus I. Laurentii Salvii, Holmiae, 828 pp.", "Scopoli, J. A. (1763) Entomologia carniolica exhibens insecta carnioliae indigena et distribute in ordines, genera, species, varietates. Methodo Linnaeana. Trattner, Vindobonae [= Vienna], 420 pp. https: // doi. org / 10.5962 / bhl. title. 119976", "De Geer, C. (1776) Memoires pour servir a l'histoire des insectes. Tome Sixieme. P. Hesselberg, Stockholm, viii + 523 pp.", "Geoffroy, E. L. (1785) Entomologia Parisiensis, sive catalogus Insectorum quae in agro parisiensi reperiuntus. Vols. 1 - 2. Via et Aedibus Serpentineis, Paris, viii + 544 pp.", "Meigen, J. W. (1822) Systematische Beschreibung der bekannten europaischen zweiflugeligen Insekten. Vol. 3. Schultz- Wundermann, Hamm, 416 pp.", "Wiedemann, C. R. W. (1824) Munus rectoris in Academia Christiana Albertina aditurus analecta entomologica ex Museo Regio Havniensi maximw congesta profert iconibusque illustrat. Eregio typoguapheo scholarum, Kiliae [= Kiel], 60 pp. https: // doi. org / 10.5962 / bhl. title. 77322", "Macquart, P. J. M. (1855) Dipteres exotiques nouveaux ou peu connus. 5. e supplement. Memoires de la Societe des Sciences, Agriculture et des Arts, de Lille, Series 2, 1, 25 - 156.", "Thomson, C. G. (1869) Diptera. Species nova descripsit. In: Kongliga Svenska Vetenskraps-Akademien, Kongliga svenska fregatten Eugenies resa omkring jorden. Pt. 2. Zoologie. [Sec.] 1. Insekter. P. A. Norstedt & Soner, Stockholm, 617 pp.", "Strobl, P. G. (1893) Die Dipteren von Steiermark I. Mitteilungen Naturwiss Verein fur Steiermark, 29, 1 - 199.", "Santos Abreu, E. (1924) Monografia de los Syrphidos de las Islas Canarias, Academia de Ciencias y Artes de Barcelona, Series 3, 19 (1), 1 - 148.", "Efflatoun, H. C. (1922) A Monograph of Egyptian Diptera. (Part I. Fam. Syrphidae). Memoires de la Societe Entomologique d'Egypte, 2, 1 - 123.", "Shaumar, N. & Kamal, S. (1978) The Syrphidae of Egypt. Bulletin Mensuel de la Societe Linneenne de Lyon, 47, 79 - 84. https: // doi. org / 10.3406 / linly. 1978.10295", "Speight, M. C. D. (2017) Species accounts of European Syrphidae (Diptera). In: Speight, M. C. D., Castella, E., Sarthou, J. - P. & Vanappelghem, C. (Eds.), Syrph the Net, the database of European Syrphidae. Vol. 97. Syrph the Net Publication, Dublin, 294 pp.", "De Buck, N. (1990) Bloembezoek en bestuivingsecologie van Zweefvliegen (Diptera, Syrphidae) in het bijzonder voor Belgie. Studiedocumenten van het K. B. I. N., Brussel, 167 pp.", "Aguilera, A., Cid, A., Regueiro, B. J., Prieto, J. M. & Noya, M. (1999) Intestinal Myiasis Caused by Eristalis tenax. Journal of Clinical Microbiology, 37 (9), 3082."]}